Polarized Neutron Reflectometry of Metal Consumption and Passive Film Growth on Nickel Exposed to an Alkaline Deuterium Oxide (D2O) Solution. Issue 12 (21st September 2017) - Ha, Hung; Fritzsche, Helmut; Burton, Gordon; Ulaganathan, Jaganathan
Abstract : Electrochemical behavior of Ni in an alkaline heavy water electrolyte was studied using cyclic voltammetry and polarized neutron reflectometry. Delays in the hydrogen and oxygen evolution reactions on Ni electrodes and slower kinetics of the reactions in heavy water compared to light water were observed. However, in both 0.01 mol/L NaOH light and heavy water solutions, Ni oxidation and passive film formation occurred at the same potential with similar passive current densities indicating a minor isotope effect of deuterium on passive film formation and growth. Polarized neutron reflectometry detected a passive film growth coefficient of 11.5 ± 1.1 Å/V. The Ni consumption coefficient was determined to be 7.3 ± 1.5 Å/V. Ni oxidation and passive film growth occurred mostly during the transient period after the applied potential increase but was negligible at the steady state. The electric field strength across the passive film was 8 × 10 6 V/cm. The Pilling-Bedworth ratio of the passive film during potentiostatic growth was close to the value of NiO grown on bulk Ni. This work demonstrated the capability of neutron reflectometry in the study of passive films on metals and alloys.